Linseed hydrogel based floating drug delivery system for fluoroquinolone antibiotics: Design, in vitro drug release and in vivo real-time floating detection - Fatima Akbar Sheikh; Muhammad Ajaz Hussain; Muhammad Umer Ashraf; Muhammad Tahir Haseeb; Muhammad Farid- (Elsevier, 2020)
Herein, we designed a novel gastroretentive drug delivery system as floating matrix tablets based on a polysaccharide material from linseeds (Linum usitatissimum L.) for fluoroquinolone antibiotics. A number of formulations were designed with a combination of linseed hydrogel (LSH) and different excipients to obtain a desired sustained release profile of moxifloxacin. The drug release study was performed basically at pH 1.2. However, the tablet may pass through the stomach to intestine due to certain reasons then it also offered sustained drug release at intestinal pH 4.5, 6.8 and 7.4, as well. Results indicated that sustained moxifloxacin release was directly proportional to the concentration of LSH and the release of drug followed non-Fickian diffusion. SEM of the tablets indicated porous nature of LSH with elongated channels which contributed to the swelling of the tablet and then facilitated the discharge of moxifloxacin from the core of the tablet. In vivo X-ray study was performed to assess disintegration and real-time floating of tablet that confirmed its presence for 6 h in the stomach. These findings indicated that LSH can be used to develop novel gastroretentive sustained release drug delivery systems with the double advantage of sustained drug release at all pH of GIT.